The use of transrectal ultrasound-guided biopsy following the introduction of prostate-specific antigen testing in Denmark: a population-based analysis. (4th May 2018) - Klemann, Nina; Røder, Martin Andreas; Helgstrand, John Thomas; Brasso, Klaus; Toft, Birgitte G.; Vainer, Ben; Iversen, Peter
Abstract: Objective: Incidence rates of prostate cancer in Denmark resemble those of countries that endorse prostate-specific antigen (PSA) screening. So far, no studies have described the consequences of PSA testing on diagnostic activity on a population level. The aim of this study was to describe the frequency of systematic transrectal ultrasound-guided biopsy (TRUS-gb) activity, including rebiopsy rates, in Denmark between 1995 and 2011. Materials and methods: All men who underwent TRUS-gb during the period were identified in the Danish Prostate Cancer Registry. In total, 83, 041 biopsy sets from 64, 430 individuals were identified. The diagnostic rate and the frequency of rebiopsy were analyzed. Age, histology and PSA were compared at the time of biopsy. Results: The number of TRUS-gb per 100, 000 men per year increased 4.6-fold. The mean number of TRUS-gb procedures per individual increased from 1.08 in 1995 to 1.46 in 2011 ( p  = .0001), and the proportion of men with negative initial biopsy sets who underwent rebiopsy increased from 22% in 1995 to 41% in 2004, later decreasing to 31% in 2009. Conclusions: The diagnostic activity in Denmark and the rebiopsy rates in men with initial negative TRUS-gb have increased substantially, and guidelines for the management of men with a negative initial biopsy are highly warranted.